THE EFFECT OF CAPITAL STRUCTURE AND LIQUIDITY ON PROFITABILITY BEFORE AND DURING THE COVID-19 PANDEMIC IN TELECOMMUNICATION COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Novie Wulan Sari; Mokhamad Anwar; Yudi Ahmad Faisal (Jurnal Bisnis Manajemen, 2022)
This study examines the effect of capital structure and liquidity on profitability before and during the Covid-19 pandemic in telecommunications companies listed on the Indonesian stock exchange. In knowing how much profit a company gets, it can be seen from its financial performance, especially in the capital structure as measured by DER and liquidity as measured by CR. Capital structure will affect profitability as measured by ROE, this is because the maximum use of debt will reduce interest payments because companies are required to pay higher interest. While liquidity affects profitability because high liquidity will increase the credibility of the company which will make investors interested in investing in efforts to increase profitability. In calculating profitability, we can find out the level of profit the company earned before and during the Covid-19 Pandemic. The purpose of this study is to determine the comparison between capital structure and liquidity on profitability. This study uses telecommunications companies listed on the Indonesia Stock Exchange in Q1 2018 - Q2 2022. The type of data used is secondary data. The results of this study indicate that prior to the Covid-19 pandemic, capital structure had a negative and significant effect, and liquidity had a positive and insignificant effect on profitability. Meanwhile, during the Covid-19 pandemic, capital structure had a positive and significant effect and liquidity had a positive and significant effect on profitability.